2014
DOI: 10.1007/s12034-014-0707-9
|View full text |Cite
|
Sign up to set email alerts
|

High pressure phase transitions for CdSe

Abstract: The structure and pressure-induced phase transitions for CdSe are investigated using firstprinciples calculations. The pressure-induced phase transition sequence WZ/ZB → Rs → Cmcm → CsCl for CdSe is drawn reasonably for the fist time, the corresponding transition pressures are 3.8, 29 and 107 GPa, respectively and the intermediate states between the Cmcm structure and the CsCl structure should exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…When the pressure reached roughly 6.99 GPa, we noted that a phase transformation occurred. The emergence of a new small peak at about 12.5° and the disappearance of a peak at about 20° suggested that the Zb-CdSe NCs underwent a phase transition from a Zb structure to a rocksalt (Rs) structure at about 6.99 GPa, which was in accordance with the theories . This phase transition from a direct band gap Zb structure to an indirect band gap Rs structure explained why the emission band is basically quenched above 6.99 GPa that was mentioned before.…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When the pressure reached roughly 6.99 GPa, we noted that a phase transformation occurred. The emergence of a new small peak at about 12.5° and the disappearance of a peak at about 20° suggested that the Zb-CdSe NCs underwent a phase transition from a Zb structure to a rocksalt (Rs) structure at about 6.99 GPa, which was in accordance with the theories . This phase transition from a direct band gap Zb structure to an indirect band gap Rs structure explained why the emission band is basically quenched above 6.99 GPa that was mentioned before.…”
Section: Results and Discussionsupporting
confidence: 88%
“…A lot of researchers make efforts to improve the emission of NCs including surface passivation with shells, laser radiation, and synthesis using different ligands. It is also found that the stable chirality can improve the optical properties of NCs. Nevertheless, the success in increasing the PL intensity and adjusting the band gap of Zb-CdSe NCs has still been limited. Likewise, high pressure is an effective way that we can use to determine the band structures or phase stabilities and enhance the fluorescence. Many other reports are referred to generate novel materials by using the pressure. Examples of successful synthesis even extend to high-pressure metastable phases. Zb-CdSe NCs have better optical properties than Wz-CdSe NCs; however, most high-pressure research studies are confined to Wz-CdSe NCs and only focused on the pressure-induced structural phase transition of CdSe NCs. There are few reports on the pressure-dependent optical behaviors of the Zb-CdSe NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the theoretical and experimental band structures of CdS and CdSe under high pressure were determined by Cervantes et al [6]. Kong group [7] investigated the crystal structure and structural phase transitions for CdSe under high pressure. Additionally, the conversion of spheroidal shaped arrays of CdSe nanocrystal into 1D luminescent nanowire under high pressure was reported by Li and coworkers [8].…”
Section: Introductionmentioning
confidence: 99%